Corporate Foresight Preparedness: Bridging organisational and individual perspectives on foresight - Grabtchak, Anna (My University, 2023)
Understanding how to increase foresight capabilities within an organisation has long been a target for organisations and researchers operating in the field of corporate foresight. While many agree on the importance of the target, the efforts taken seem to reveal a gap between motivated movement towards the target and reaching the actual results. Connecting the strategic foresight policies to practices conducted by individuals, and able learning by making foresight an embedded continuous activity that seamlessly supports other processes in the organisation, is challenging. Corporate Foresight Preparedness helps to define an organisation’s foresight development needs by comparing a level of foresight maturity with the level of foresight need. However, it shows only one side of the coin, the organisational perspective. The other side could be illuminated by taking the perspective of individuals in the organisation. Futures Consciousness, one of the latest metrics developed to measure the level of a person’s foresight thinking, was used to understand the issue from an individual’s perspective. Bringing these perspectives provided a more thorough picture of the issue of foresight development, thus in this research, foresight in a case company is studied as a system formed by an organisation and its individuals. A mixed methods approach is used to interconnect qualitative and quantitative research methods for a holistic overview formation on the foresight development needs. This research aims to: Provide an overview of foresight development needs by summarizing the foresight success factors, map the current state of foresight in the case company and the development topics based on a systemic view of individual and organisational factors. Here, the strategic level of foresight is connected with the practical side to answer the main research question: How to develop successful foresight practices in Company X? The results based on empirical data gathered from 22 in-depth interviews and 143 survey answers show that individuals in the case company struggle with low Agency beliefs, it is hard for them to be open to alternatives in their futures thinking, in addition, the organisation’s method sophistication and the culture are not supporting foresight development sufficiently enough. The main finding was that foresight should be embedded into the organisation’s culture and methods sophistication to provide better agency for the individuals and assist in conducting foresight practices in line with foresight targets and policies set from the organisation’s strategic perspective.
Keywords: Corporate Foresight Preparedness, Futures Consciousness